A Comparison of Pregnancy Outcomes Using Two Diagnostic Criteria for Gestational Diabetes Mellitus-Carpenter Coustan Criteria and International Association of the Diabetes and Pregnancy Study Groups (IADPSG) Criteria* - Tahmina, Sultana (Journal of the ASEAN Federation of Endocrine Societies, 2017)

(untitled) (J ASEAN Fed Endocr Soc)
OBJECTIVE: To compare the maternal and perinatal outcomes in women with GDM diagnosed by Carpenter & Coustan (CC) criteria and by the International Association of the Diabetes and Pregnancy Study Groups (IADPSG) criteria. METHODOLOGY: A cross-sectional comparative study was conducted using data of women who were screened and diagnosed with GDM between April 2006-March 2007 using the CC criteria and April 2013-March 2014 using IADPSG criteria. Maternal and perinatal outcomes were noted. Means and proportions were calculated for continuous and categorical variables respectively. Data were analyzed using t-test for normally distributed data and Mann-Whitney U test for those that were not normally distributed. Pearson Chi-square test was used to find an association between the various outcomes between the two groups. RESULTS: Among 500 pregnant women screened, 36 were diagnosed GDM in the CC group. In the IADPSG group, 733 women were screened and 167 were diagnosed GDM. Prevalence of GDM was 7.2% in CC group and 22.78% in IADPSG group (p=0.000). There was a statistically significant difference in the number of women who developed hypertension and polyhydramnios among the two groups. Women who had an operative vaginal delivery (16.67% vs. 6.6%, p=0.085) and mean birth weight (3.10 ± 0.55 kg vs. 2.97 ± 0.48 kg, p=0.165) were higher in CC group than the IADPSG group. Among the perinatal outcomes, a statistically significant improvement was found in the number of neonates developing respiratory distress syndrome (p=0.000) and hyperbilirubinemia (p=0.000), when the IADPSG criteria were used. CONCLUSIONS: There is a statistically significant difference between the maternal and neonatal outcomes when the newer IADPSG criteria were used for diagnosis of GDM.